Memperkenalkan Penggunaan Media Youtube Sebagai Bahan Ajar Bahasa Inggris Di Sekolah Menengah Pertama - Abdul Syahid; Muhammad Hidayatur Rahman; Weni Wulandari; Muhamad Ario Setiawan; Adinda Aulia Rahmah; Noor Muti’ah; Syarif Hidayat (Jurnal Pengabdian Masyarakat Nusantara, 2023)
The English language, as a universal language, plays a crucial role in global communication. This research explores the contribution of modern media to vocabulary development, considering that English is taught at various education levels in Indonesia. Vocabulary development is not only the responsibility of the classroom but also involves learning strategies outside the class, including the use of media like YouTube. YouTube serves as an engaging learning tool, especially to overcome difficulties in understanding English lessons that may be challenging through textbooks and worksheets. Enjoyable media like YouTube can have a positive impact on learning and student engagement. This study was conducted at MTs Terpadu Berkah in Central Kalimantan, Palangka Raya. The service-based implementation method involved preparing vocabulary materials, with YouTube chosen as the teaching tool. The service process required permission from the school principal and was carried out during the learning sessions. The results indicated that students found the use of YouTube more interesting and effective for learning English. In conclusion, this approach could be further integrated into English teaching in various schools as a new and engaging alternative.